2014
DOI: 10.1039/c4ra04262j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the local environment of Sm3+ in doped SrZrO3 and energy transfer mechanism using time-resolved luminescence: a combined theoretical and experimental approach

Abstract: A combined experimental and theoretical study on the photoluminescence (PL) properties of strontium zirconate (SZ) and Sm3+ doped SZ nanostructures is presented in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 69 publications
4
74
1
1
Order By: Relevance
“…These results is in concordant with our emission studies where we have observed that majority of Sm 3 þ ions occupying Ba 2 þ site without inversion symmetry. Such site selective luminescence of lanthanide in host such as Sr 2 SiO 4 , Zn 2 P 2 O 7 , SrZrO 3 and Sr 2 CeO 4 where multiple sites are available for occupancy has already been reported by our group [46][47][48]53]. Fig.…”
Section: Lifetime Spectroscopy Of Sm 3 þ Doped Bazromentioning
confidence: 64%
See 2 more Smart Citations
“…These results is in concordant with our emission studies where we have observed that majority of Sm 3 þ ions occupying Ba 2 þ site without inversion symmetry. Such site selective luminescence of lanthanide in host such as Sr 2 SiO 4 , Zn 2 P 2 O 7 , SrZrO 3 and Sr 2 CeO 4 where multiple sites are available for occupancy has already been reported by our group [46][47][48]53]. Fig.…”
Section: Lifetime Spectroscopy Of Sm 3 þ Doped Bazromentioning
confidence: 64%
“…In case of Sm 3 þ ; 4 G 5/2 -6 H 7/2 (ΔJ ¼ 7 1) is a partly magnetic dipole (MD) and partly electric dipole(ED) emission band whereas 4 G 5/2 -6 H 5/2 is purely MD and 4 G 5/2 -6 H 9/2 is purely ED natured [48].The magnetic dipole transition (MDT) 4 G 5/2 -6 H 5/2 does not depend on chemical surroundings of the luminescent centre and its symmetry. However, the hypersensitive 4 G 5/2 -6 H 9/2 transition is magnetic-dipole forbidden and electricdipole allowed and its intensity increases as the environmental symmetry become lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probably these defect states or disorders that are instrumental behind this luminescence behaviour exhibited by GdScO 3 . There is a lot of literature on the existence of defect mediated luminescence in perovskite structure like SrTiO 3 [19], PbZrO 3 [20], BaZrO 3 [21], PbTiO 3 [22], CaTiO 3 [23], MgTiO 3 [24], SrZrO 3 [25][26][27] etc. In order to have a better understanding of the PL behaviour exhibited, the PL curves were analysed by PEAKFIT deconvolution.…”
Section: Optical Properties Of Undoped Gdscomentioning
confidence: 99%
“…For various optoelectronic applications, alkaline-earth perovskite structured MZrO 3 (M = Sr, Ba, Ca) are attractive candidates because of their high thermal as well as chemical stability and eco friendly nature192021. The displacement of Zr or M atoms in disordered perovskite MZrO 3 may induce some vacancy defects at the axial and planar oxygen sites of the [ZrO 6 ] octahedral19.…”
mentioning
confidence: 99%